DOI: 10.31979/etd.tanp-8252
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Communication, Workflow Efficiency, & Patient Care Quality Resulting from a Hands-free, Wireless Communication Device

Abstract: I would like to convey my heartfelt thanks to my doctoral project chair. Dr. Danette Dutra, and my mentor, Dr. Nicolette Estrada. I will always be grateful for all the guidance and support you so generously gave throughout this journey. Your wisdom has helped shape this project. Thank you to my committee member, Revena Gantuangco, for her support and friendship. Montina Dudley-Alford and Jacob Nur, for their invaluable assistance in the implementation of this project. Also, my aunt Norma McCurdy, for her phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…This finding is consistent with findings from another study that showed that nurses used language, gestures, education, and relationship-building to reassure patients [39]. Another study also revealed the need for nurses to remain calm when their patients are angry [40]. Reassurance should be used tactfully since, offering false reassurance goes against the principle of veracity which could lead to mistrust, conflicts, and non-adherence to treatment.…”
Section: Therapeutic Communication Practicessupporting
confidence: 83%
“…This finding is consistent with findings from another study that showed that nurses used language, gestures, education, and relationship-building to reassure patients [39]. Another study also revealed the need for nurses to remain calm when their patients are angry [40]. Reassurance should be used tactfully since, offering false reassurance goes against the principle of veracity which could lead to mistrust, conflicts, and non-adherence to treatment.…”
Section: Therapeutic Communication Practicessupporting
confidence: 83%